Evaluation of Nasal Mucociliary Activity in Patients with Psoriasis Vulgaris - Dundar, Mehmet Akif; Temiz, Selami Aykut; Tuncez, Ismail Hakki; Emre, Elif; Emre, Sadettin; Dursun, Recep (Mattioli 1885, 2025)
Introduction: Psoriasis, a chronic inflammatory dermatological condition, is marked by recurring periods of activity and quiescence. This persistent inflammation contributes to a range of associated health issues. The respiratory system relies on nasal mucociliary clearance as a fundamental defense mechanism. Mucociliary transport dysfunction is frequently observed in chronic inflammatory states. Objective: We aimed to determine the relationship between psoriasis and concomitant clinical conditions and nasal mucociliary clearance time (NMCT). Method: We conducted a study to evaluate NMCTin 34 individuals diagnosed with psoriasis and control group of 35 healthy individuals. Results: Our results revealed a statistically significant prolongation of NMCT in the psoriasis group (11.26 +/- 2 minutes) compared to the control group (9.2 +/- 1.85 minutes, P<0.001). Moreover, a positive correlation was identified between NMCT and both the duration of psoriasis and the Psoriasis Area and Severity Index (PASI). This suggests that impaired nasal mucociliary clearance in individuals with psoriasis, especially those with more severe disease, may elevate their vulnerability to infections of the sinuses and nasal passages. Conclusion: This highlights the need to consider strategies for enhancing mucociliary function in patient population.
Keywords: Psoriasis; Nasal Mucociliary Clearance; Inflammation; Respiratory Infection; Comorbidity